Metal-Free Cascade Synthesis of 1,2,4-Thiadiazoles from β-Ketothioamides and Alkyl/Aryl Cyanides under TBN Enabling Conditions at Room Temperature - Singh, Saurabh; Shukla, Gaurav; Ray, Subhasish; Singh, Maya Shankar (Synthesis, 2023)
A metal-free radical cascade cyclization of β-ketothioamides and alkyl/aryl cyanides has been developed for the synthesis of 1,2,4-thiadiazoles bearing a stable nitroso group at an exocyclic double bond in a one-pot system. The reaction proceeds via the in situ generated ketoxime intermediate of β-ketothioamide, which further assists the formation of 1,2,4-thiadiazole through reaction with nitrile under TBN (tert-butyl nitrite) mediation. The basic utility of this reaction is the formation of three new bonds (two C–N and one S–N) in one stretch under mild conditions. Moreover, this protocol features excellent functional group tolerance, operational simplicity, and easy scalability. The radical process is supported by the BHT adduct of the α-ketoxime intermediate. Noteworthy is that the products possess Z stereochemistry with regard to the exocyclic C=C double bond at the 5-position.
Keywords: radical reactions; cyclization; metal-free; 1,2,4-thiadiazoles; chemoselectivity